Non-syndromic multiple odontogenic keratocysts associated with dental anomalies: A report of unusual case and its management - Sulabha A Narsapur; Sameer Choudhari; Neelkant M Warad; Shankar Manjunath (Wolters Kluwer Medknow Publications, 2015)
Odontogenic keratocyst (OKC), now known as keratocystic odontogenic tumor (KCOT), is the most common cystic lesion occurring in the maxillofacial region. Multiple occurrence of these cysts is less frequent and is usually associated with syndromes, the most common being the Gorlin Goltz syndrome or the nevoid basal cell carcinoma syndrome (NBCCS). We hereby report an unusual case of multiple OKCs in a healthy adult, associated with other dental anomalies. Management approach consisted of enucleation with curettage of the smaller lesions and decortication of buccal cortex in the large lesion. The condition in the present case may be because of the multifocal nature of OKC rather than its association with any syndrome. Concomitant occurrence of multiple OKCs with other dental anomalies may be coincidental. Impacted teeth or missing teeth must be radiographed to rule out the lesions associated with them.